Evaluation of the Impact of the Peregrine Falcon (Falco peregrinus peregrinus) Reintroduction Process on Captive-Bred Population - Karol O. Puchała; Zuzanna Nowak-Życzyńska; Sławomir Sielicki; Wanda Olech (Genes, 2022)
The main objective of this study was to determine the impact of increased demand for peregrine falcons via breeding (mainly Polish, Czech, German and Slovak) on the genetic structure of the birds. In the analysis, 374 specimens from six countries were sampled in 2008–2019 (omitting 2009), and all the birds analyzed were released into the wild as part of the Polish reintroduction program. The assessment of genetic variation was based on a well-known panel of 10 microsatellite markers described for the species. We calculated a fixation index for the samples from each year, and based on this, we determined the level of inbreeding. We also performed an analysis using the Bayesian cluster method, assuming that 1–19 hypothetical populations would define the division that best fit the samples. The most probable division was into two groups; in the first group, the samples from individuals delivered in 2013 were most often segregated; moreover, in this year, a jump in inbreeding, expressed by the fixation index, was observed.